2016
DOI: 10.1111/bor.12164
|View full text |Cite
|
Sign up to set email alerts
|

Using GIS and streamlined landforms to interpret palaeo‐ice flow in northern Iceland

Abstract: The properties of streamlined glacial landforms and palaeo-flow indicators in the valleys of Viðidalur, Vatnsdalur and Sv ınadalur in northern Iceland were quantified using spatial analyses. Drumlins and mega-scale glacial lineations (MSGL) were visually identified using satellite imagery from Google Earth, the National Land Survey of Iceland (NLSI) Map Viewer and Landsat satellites, and using aerial photographs from the NLSI. A semi-automated technique was developed using ENVI to determine regions in northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 60 publications
6
38
0
1
Order By: Relevance
“…Over the last ~15 years there has been increasing use of DEMs in glacial geomorphology, particularly for mapping at the ice-sheet scale (e.g. Hughes et al, 2010;Ó Cofaigh et al, 2010;Evans et al, 2014Evans et al, , 2016dPrincipato et al, 2016;Ojala, 2016;Stokes et al, 2016a;Mäkinen et al, 2017;Norris et al, 2017). DEMs are raster-based models of topography that record absolute elevation, with each pixel or grid cell in a DEM representing the average height for the area it covers (Clark, 1997;Smith et al, 2006).…”
Section: Digital Elevation Modelsmentioning
confidence: 99%
“…Over the last ~15 years there has been increasing use of DEMs in glacial geomorphology, particularly for mapping at the ice-sheet scale (e.g. Hughes et al, 2010;Ó Cofaigh et al, 2010;Evans et al, 2014Evans et al, , 2016dPrincipato et al, 2016;Ojala, 2016;Stokes et al, 2016a;Mäkinen et al, 2017;Norris et al, 2017). DEMs are raster-based models of topography that record absolute elevation, with each pixel or grid cell in a DEM representing the average height for the area it covers (Clark, 1997;Smith et al, 2006).…”
Section: Digital Elevation Modelsmentioning
confidence: 99%
“…Most Icelandic cross-shelf troughs terminate with a reverse slope in long-profile and a bulging, arcuate terminus in planform ( Figure 2C). Their association with distinct sets of large submarine streamlined ridges, running parallel to trough axes, as well as similar streamlined mega-lineations and striae onshore (Norðdahl, 1991;Bourgeois et al, 2000;Principato et al, 2016), strongly suggest that these areas were regions of streaming ice flow, indicative of widespread temperate subglacial conditions. Often associated with these offshore mega-lineations, are parallel channels up to 75 m in depth, 3 km wide and 20 km long, found incising to depths of 360 m below present-day sea level.…”
Section: Shelf-edge Glaciation?mentioning
confidence: 91%
“…Glacial lineations are a common landform signature of palaeo-ice sheets, indicative of fast, icestreaming flow (Clark, 1993;Ó Cofaigh et al, 2002;Stokes and Clark, 2002;King et al, 2009), and have been readily identified across the Icelandic shelf to infer the presence of numerous ice streams that drained ice towards the shelf edge and an ice divide across central Iceland from east to west (Bourgeois et al, 2000;Stokes and Clark, 2001;Spagnolo and Clark, 2009;Principato et al, 2016).…”
Section: Ice-flow Directions and Ice Limitsmentioning
confidence: 99%
“…The H unafl oi/Reykjafjarda all Trough (HT, Fig. 1A) provided a bathymetric outlet for a major ice stream that flowed northward to the Iceland Sea (Bourgeois et al, 2000;Hubbard, 2006;Principato et al, 2016;Patton et al, 2017). Core B997-326PC1 ( Fig.…”
Section: Grain-size Spectramentioning
confidence: 99%